Green Taxonomy for Sustainable Production Across Countries - Dariah, Atih Rohaeti; Rani, Asni Mustika; Srisusilawati, Popon (KnE Social Sciences, 2023)
The green taxonomy plays a central role in driving developments in sustainable finance, leading to the achievement of sustainable production goals in various countries. While some countries have already adopted a green taxonomy, others are in the process of developing one. This study aims to identify the countries that have implemented sustainable finance in different forms and to conduct a content analysis to compare and identify gaps in their green taxonomy implementations. The research reveals that several countries worldwide have embraced the green taxonomy as a crucial tool in advancing sustainable finance and promoting sustainable production. These countries generally have specific environmental goals, establish green finance-related institutional arrangements and financial products, and compile lists of economic sectors and activities covered under the green taxonomy. Key sectors addressed by the green taxonomy include agriculture, energy, manufacturing industries, and transportation. However, each country still maintains its unique approach to environmental protection efforts through the use of green taxonomy tools. Keywords: green taxonomy, sustainable finance, sustainable production